1990
DOI: 10.1021/bi00463a024
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active metal-independent superoxide dismutase mimics

Abstract: Superoxide dismutase (SOD) is an enzyme that detoxifies superoxide (O2.-), a potentially toxic oxygen-derived species. Attempts to increase intracellular concentrations of SOD by direct application are complicated because SOD, being a relatively large molecule, does not readily cross cell membranes. We have identified a set of stable nitroxides that possess SOD-like activity, have the advantage of being low molecular weight, membrane permeable, and metal independent, and at pH 7.0 have reaction rate constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
226
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 417 publications
(237 citation statements)
references
References 25 publications
8
226
0
1
Order By: Relevance
“…While the SOD mimetic activity of nitroxides was recognized in the initial studies, the multiple modes by which this class of agents provides protection was first reported in 1990 [13]. In this study, several nitroxides and their corresponding hydroxylamines were tested for protective effects in Chinese hamster V79 lung fibroblasts exposed to hypoxanthine/ xanthine oxidase under aerobic conditions.…”
Section: Cellular Protection Against Oxidative Damagementioning
confidence: 97%
See 2 more Smart Citations
“…While the SOD mimetic activity of nitroxides was recognized in the initial studies, the multiple modes by which this class of agents provides protection was first reported in 1990 [13]. In this study, several nitroxides and their corresponding hydroxylamines were tested for protective effects in Chinese hamster V79 lung fibroblasts exposed to hypoxanthine/ xanthine oxidase under aerobic conditions.…”
Section: Cellular Protection Against Oxidative Damagementioning
confidence: 97%
“…Nitroxides can prevent generation of • OH radicals from Fenton reactions by accepting the electron from the reduced metal complex as shown in equation 6c [13].…”
Section: Inhibiting Fenton Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cholestane and cholic acid nuclei were chosen as representatives of less (cholestane) and more polar (cholic acid) steroidic moieties. The IK-1/IK-2 activity was compared with that of known antioxidants: TEMPO, chosen for its ability to react mainly with primary radicals, (Mitchell et al, 1990;Voest et al, 1994;Nilsson et al, 1989) and h-tocopherol for its chain-breaking antioxidant capability (Niki, 1987;Halliwell et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these have shown that simple nitroxyl radicals, previously used as spin labels for electron spin resonance spectroscopy, are able to inhibit lipid peroxidation in various ways. In fact these nitroxyl radicals react with, and dismutate, superoxide radical anions (O 2 − ) in a catalytic fashion that mimics that of superoxide dismutase (Mitchell et al, 1990;Samuni et al, 1991), competing with H 2 O 2 in the oxidation of Fe 2 + ions (Voest et al, 1994) and preventing hydroxyl radical (OH ) formation (Gelvan et al, 1991). However some of these simple nitroxyl radicals show, together with these favourable effects, undesirable properties like negative chronotropy and anaesthetic effects that prevent their use in pharmacology (Gelvan et al, 1991).…”
Section: Introductionmentioning
confidence: 99%